Outcome of Percutaneous Coronary Intervention Among Very Elderly Patients with Ischemic Heart Disease - A K Al Miraj; Quazi Deen Mohammad; Sharfuddin Ahmed; Muhammad Kamal Hossain; Mohammad Rashal Chowdhury; Muhammad Ata Ullah (International Journal of Heart Research, 2022)
Background Cardiovascular disease, and ischemic heart disease (IHD), is a major cause of morbidity and mortality in the very elderly patients worldwide. In the developing countries like Bangladesh it has been increasing with time. Due to life style, food habits and urbanisation. These patients represent a rapidly growing cohort presenting for percutaneous coronary intervention (PCI), now constituting more than one in five patients treated with PCI in real-world practice. Materials and Methods From July 2020 we included 152 patients with IHD purposively in Cardiology department of Bangabandhu Sheikh Mujib Medical University Dhaka, Bangladesh undergone PCI who were divided into 2 groups according to age: e” 75 years (n = 51) and <75 years (n = 101). Baseline clinical characteristics, indications for coronary intervention, in hospital outcomes were obtained. Study endpoint was Renal impairment, MI, LVF, emergency revascularization and death. Results Very elderly patients were more frequently male (86.2%) and nonsmoker at present (41.1% vs. 63.3%, p=0.003), had higher prevalence of hypertension (60.7% vs. 50.4%, p<0.13), and more often presented with NSTEMI (54.9% vs. 23.7%, p<0.001). Elderly group had higher incidence of TVD and LM disease (37.2% vs. 26.7% and 9.8% vs. 2.9%, p=0.07) and more incidence of ostial (17.6% vs.5.9%,p=0.007) and calcified lesions (31.3% vs. 14.8%, p=0.004). Procedural success (TIMI III) were high in both groups, but still lower in the elderly as compared to younger group (96% vs. 97%, p=0.65). Very elderly patients had higher incidence of post PCI bleeding, CIN, MI, LVF and death (9.8% vs.5.9%, 7.8% vs.3.9%, 5.8% vs.5.9%, 9.8% vs. 4.9% and 5.8%vs.3.9%,p=0.07), whereas emergency revascularization were higher in younger group (5.8% vs. 6.9%, p=0.07). Conclusion Very elderly patients aged ≥80 years face more vascular site complications during PCI, usually have more LM and TVD with more ostial and calcified lesions in comparison with younger group. Though procedural success is similar with younger group, they face more post PCI CIN, LVF and MI. Repeat revascularization was higher in younger group.
Keywords: Outcome of PCI